The Effect of Cow Biourin With Differences Dose on Spirulina sp. - Esti Meliana Manalu; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted in September- October 2019 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University, Pekanbaru. The purpose of this study was to determine the best dose of cow biourin in increasing the growth rate and biomass production of Spirulina sp.. The method used in this research was experimental using Completely Random Design (CRD) one factor with four treatments and repeated three times. The treatments used was  Walne 1ml/L  (Control) , Biourin-1,5 ml/L , Biourin-3,5 ml/L and Biourin-5,5 ml/L. Cultivation was carried out for nine days, using biurin and Walne . The results showed that the treatment of the of  cow biourin with  differences dose affected the population density and specific growth rate. Biourin-5,5 ml/L gave the best results with a cell density of 337,5 x 104 cells / ml and a specific growth rate of 0,76214/ day with peak growth occurring on the day seven. Water quality parameters during the study were optimal for the growth of Spirulina sp.with a water temperature of 29-33 0C, pH 7-8.9 and dissolved oxygen 8-8.5 mg / l. Keywords: Biourin, Spirulina sp, Dose.